THE EFFECTIVENESS OF INTERACTIVE DIGITAL ENGLISH BOOK FOR READING SKILL IN TENTH GRADE STUDENTS AT MA MASALIKIL HUDA - Faurismawan, Jovan Syach; Mubarok, Husni (Universitas Suryakancana, 2024)
Reading, which involves character decoding, is a complex cognitive process with the goal of understanding the text. Reading in English gives students the opportunity to pursue interest and knowledge in learning English. Reading is a way to teach other speaking skills. Most students are quiet during lessons because they find learning boring. Therefore, teachers need media that makes the learning process more interesting. The purposeiof this study was to determine the effectiveness of the Interactive Digital English Book (IDEB) in improving students' reading skills. This study was conducted on 42 MA Masalikil Huda Jepara tenth-grade students who were divided into two classes. This research is a quantitative type of researchiusing quasi-experimental prei- test and posti- test research methods. The dataithat came from the research were gathered using tests in the form of multiple-choice tests for the students. The average score for the experimental group that has been calculated is 74.5 points and that of the control group was 55.7 points. T-Analysis Results: Sig. (2-tailed) is 0.07, greater than 0.05, besides that the T-test is greater than the T-tablei(2.201 > 2.021). As a result, the use of English Digital Textbooks has been found to be effective in improving students' reading skills.